ANALISIS PENGARUH MEDAN MAGNET TERHADAP UKURAN ATOMISASI BAHAN BAKAR CAMPURAN GASOLINE DAN BIOETANOL - Nufus, Tatun Hayatun; Dianta Mustofa Kamal; Gun Gun R Gunadi; Candra Damis Widiawati; Asep Apriana; Muhammad Todaro (Jurnal Rekayasa Mesin, 2024)
The atomization process plays a very important role because the success or failure of combustion in the combustion chamber is influenced by the size of the liquid fuel mist. The occurrence of good atomization from atomized is determined by the size of the fuel droplets and the size of the nozzle diameter. Reducing the droplet diameter can increase the velocity, which can affect the Reynolds number and cause turbulence effects. The effect of turbulence provides a vortex effect, which enhances the heat transfer process between hot air and fuel particles in the combustion chamber. In this research, the effect of fuel magnetization on droplet size is analyzed. The fuel used is E0, E10, E20, E30, and E100, all types of fuel are channeled through an electromagnetic field of 1500 Gauss. Next, the particle size was tested using a Particle Size Analyzer, Bettersize BeNano 90 Zeta. The result was a decrease in particle size of 8-27%. The particle size measured using the PSA (particle size analysis) tool and theoretical calculations is <10% different. Each tool has an accuracy limit for PSA with a maximum accuracy of around 5%. These results provide initial information that the fuel magnetization process can improve engine performance.